2002
DOI: 10.1021/jm010330+
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships for Pyrido-, Imidazo-, Pyrazolo-, Pyrazino-, and Pyrrolophenazinecarboxamides as Topoisomerase-Targeted Anticancer Agents

Abstract: Heterocyclic phenazinecarboxamides were prepared by condensation of aminoheterocycles and 2-halo-3-nitrobenzoic acids, followed by reductive ring closure and amidation. They showed similar inhibition of paired cell lines that underexpressed topo II or overexpressed P-glycoprotein, indicating a non topo II mechanism of cytotoxicity and indifference to P-glycoprotein mediated multidrug resistance. Compounds with a fused five-membered heterocyclic ring were generally less potent than the pyrido[4,3-a]phenazines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(72 citation statements)
references
References 16 publications
1
70
0
1
Order By: Relevance
“…The trifluoromethylsubstituted compounds have been reported to possess biological activities as herbicides [16], fungicides [17], analgesic agents [18], antipyretic agents [19], and inhibitors for platelet aggregation [20]. Recently, much attention has been focused on pyrazoles as antvirial and anticancer agents after the discovery of the pyrazole C-glycoside pyrazofurin [21,22]. This report describes the synthesis and anticancer evaluation of several trifluoromethyl-substituted pyrazole N-nucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…The trifluoromethylsubstituted compounds have been reported to possess biological activities as herbicides [16], fungicides [17], analgesic agents [18], antipyretic agents [19], and inhibitors for platelet aggregation [20]. Recently, much attention has been focused on pyrazoles as antvirial and anticancer agents after the discovery of the pyrazole C-glycoside pyrazofurin [21,22]. This report describes the synthesis and anticancer evaluation of several trifluoromethyl-substituted pyrazole N-nucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…Nitration of 1-chloroisoquinoline (2) using a mixture of nitric and sulfuric acids gave 1-chloro-5-nitroisoquinoline (3). 20 Treatment of 3 with 7 N ammonia solution in methanol led to nucleophilic displacement and formation of 1-amino-5-nitroisoquinoline (4). Reaction of 4 with the appropriate aryl isocyanate derivatives afforded the corresponding diarylurea derivatives 5a-t.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, suksdorfin (96), another natural compound isolated from the fruit of Lomatium suksdorfii, exhibits a significant anti-HIV activity as it inhibits the viral replication in the T-cell line with an EC50 in the 2.5 µM range [116] (Figure 8). In a similar approach, Wang et al [118] have reported a new one-pot two-step tandem synthesis of highly functionalized benzo[a]pyrano [2,3- [119][120][121]. This reaction was achieved by the simple condensation of 2-hydroxynaphthalene-1,4-dione (104), diamines 105, aldehydes 107 and malonitrile (108).…”
Section: Benzopyrones: Coumarins and Chromonesmentioning
confidence: 99%
“…In a similar approach, Wang et al [118] have reported a new one-pot two-step tandem synthesis of highly functionalized benzo[a]pyrano [2,3- [119][120][121]. This reaction was achieved by the simple condensation of 2-hydroxynaphthalene-1,4-dione (104), diamines 105, aldehydes 107 and malonitrile (108).…”
Section: Benzopyrones: Coumarins and Chromonesmentioning
confidence: 99%